Clinical and radiological outcomes of the first metatarsophalangeal arthrodesis with Kirschner wires for the treatment of severe hallux valgus - Luiza Horta Barbosa; José Antônio Veiga Sanhudo (Journal of the Foot & Ankle, 2020)
Objective: To present the clinical and radiographic outcomes of metatarsophalangeal arthrodesis of the hallux with crossed Kirschner wires and cerclage for the treatment of severe hallux valgus. Methods: Twenty-nine feet of 21 consecutive patients who underwent metatarsophalangeal arthrodesis to correct severe hallux valgus between March 2011 and April 2018 were clinically and radiographically evaluated. Results: After an average follow-up period of 42 months, 17 feet (58.6%) generated a response of total satisfaction with the procedure and 12 (41.4%) a response of satisfied with reservations; none of the patients were dissatisfied. Pain assessed using the visual analog scale improved from a mean of 8 before the procedure to 1.2 at follow-up. The American Orthopaedic Foot and Ankle Society score improved from a mean of 26.5 points before the procedure to 78 points at follow-up. The hallux valgus angle improved from a mean of 38.5° in the preoperative period to 13.1° at follow-up, i.e., an improvement of 25.4°. The intermetatarsal angle improved from a mean of 18.8° in the preoperative period to 15° at follow-up. Consolidation of arthrodesis occurred in all cases, but reintervention was required to remove the hardware in 17 operated feet (58.6%). Conclusion: Metatarsophalangeal arthrodesis with crossed Kirschner wires and cerclage for the treatment of severe hallux valgus produced high rates of satisfaction, with substantial improvement in pain and functional parameters, consolidation in all cases and excellent radiological correction, but had the drawback high rate of reintervention for hardware removal. Level of Evidence IV; Therapeutic Study; Case Series.